New Materialisms: Ontology, Agency, and Politics - Coole, Diana H.; Frost, Samantha (Duke University Press, 2010)
"New Materialisms brings into focus and explains the significance of the innovative materialist critiques that are emerging across the social sciences and humanities. By gathering essays that exemplify the new thinking about matter and processes of materialization, this important collection shows how scholars are reworking older materialist traditions, contemporary theoretical debates, and advances in scientific knowledge to address pressing ethical and political challenges. In the introduction, Diana Coole and Samantha Frost highlight common themes among the distinctive critical projects that comprise the new materialisms. The continuities they discern include a posthumanist conception of matter as lively or exhibiting agency, and a reengagement with both the material realities of everyday life and broader geopolitical and socioeconomic structures. Coole and Frost argue that contemporary economic, environmental, geopolitical, and technological developments demand new accounts of nature, agency, and social and political relationships; modes of inquiry that privilege consciousness and subjectivity are not adequate to the task. New materialist philosophies are needed to do justice to the complexities of twenty-first-century biopolitics and political economy, because they raise fundamental questions about the place of embodied humans in a material world and the ways that we produce, reproduce, and consume our material environment."--Publisher's description
English
Keywords: B808-849 Philosophy- Modern- Special topics and schools of philosophy